Analyzing students’ numeracy skills in contextual problems by critical thinking and mindset - Muhammad Iqbal Iqbal; Yarman Yarman (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study aims to describe the numeracy skills of 10th-grade students in solving contextual mathematical problems, reviewed based on their critical thinking and growth mindset levels. This research employed a qualitative approach with a case study method. The subjects were 108 10th-grade students at SMA Negeri 6 Padang, Data were collected through numeracy tests, critical thinking tests, growth mindset questionnaires, and in-depth interviews. Data analysis was descriptive, referring to indicators of numeracy, critical thinking, and growth mindset. The findings show that students with high critical thinking and high growth mindset levels exhibit optimal numeracy skills, categorized as high. Students with high critical thinking but moderate growth mindset still achieved high numeracy skills, while high critical thinking but low growth mindset resulted in moderate numeracy. Conversely, students with moderate critical thinking showed varied results; high growth mindset helped improve numeracy to moderate, whereas low growth mindset worsened outcomes. Students with low critical thinking, even with a high growth mindset, still demonstrated low numeracy. The combination of low critical thinking and low growth mindset yielded the lowest numeracy results. In conclusion, students with high critical thinking have better numeracy skills in analyzing information, using problem-solving strategies, and drawing logical conclusions.